2022
DOI: 10.3389/fnins.2022.886909
|View full text |Cite
|
Sign up to set email alerts
|

Upper Limbs Muscle Co-contraction Changes Correlated With the Impairment of the Corticospinal Tract in Stroke Survivors: Preliminary Evidence From Electromyography and Motor-Evoked Potential

Abstract: ObjectiveIncreased muscle co-contraction of the agonist and antagonist muscles during voluntary movement is commonly observed in the upper limbs of stroke survivors. Much remain to be understood about the underlying mechanism. The aim of the study is to investigate the correlation between increased muscle co-contraction and the function of the corticospinal tract (CST).MethodsNine stroke survivors and nine age-matched healthy individuals were recruited. All the participants were instructed to perform isometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 82 publications
(143 reference statements)
3
18
1
Order By: Relevance
“…Following a stroke occurrence, the injured brain undergoes a reorganization process that involves recruiting pathways homologous to the damaged regions in function but distinct in anatomy, synaptogenesis, dendritic arborization, and reinforcing synaptic connections ( Rossini et al, 2003 ). Such adaptive brain changes seem to be closely related to rehabilitation and motor training, contributing to the improvement of functional outcomes ( Chen et al, 2018 ; Sampaio-Baptista et al, 2018 ; Sheng et al, 2022 ). High-intensity repetitive training is one of the principles of post-stroke rehabilitation ( Langhorne et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following a stroke occurrence, the injured brain undergoes a reorganization process that involves recruiting pathways homologous to the damaged regions in function but distinct in anatomy, synaptogenesis, dendritic arborization, and reinforcing synaptic connections ( Rossini et al, 2003 ). Such adaptive brain changes seem to be closely related to rehabilitation and motor training, contributing to the improvement of functional outcomes ( Chen et al, 2018 ; Sampaio-Baptista et al, 2018 ; Sheng et al, 2022 ). High-intensity repetitive training is one of the principles of post-stroke rehabilitation ( Langhorne et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, signals from EMG-based robot can reflect the voluntary movement intention of patients in real time ( Rong et al, 2015 ; Zhuang et al, 2021 ), which may increase active patient participation and promote interaction between humans and machines. Recording of muscle activity by EMG has proved to be helpful to explore the activity state of muscle tissue and the control mechanism of the nervous system under different task states after stroke ( Ma et al, 2017 ; Chen et al, 2018 ), and then be useful for evaluating central and peripheral determinants of motor dysfunction which facilitates the understanding of mechanism behind rehabilitation intervention ( Sheng et al, 2022 ; Li et al, 2023 ). Voluntary motor intention is crucial in the rehabilitation of motor function after stroke ( Yang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The CCI can evaluate the degree of upper limb muscle activation and muscle coordination ( Sheng et al, 2022 ). As shown in Figure 7 , the results revealed that the CCI of EMG signals increased significantly in both dominant and non-dominant sides with higher MVC force.…”
Section: Discussionmentioning
confidence: 99%
“…The CPL− condition increased by 47% (95% CI 41-52) per mA. SB− increased by 46% (95% CI 41-52) per mA, while SB+ increased by similarly by 41% (95% CI [35][36][37][38][39][40][41][42][43][44][45][46]. The CPF+ increased by 33% (95% CI 27-39) per mA and CPL+ increased by 28% (95% CI 23-34) per mA.…”
Section: Mep Responsementioning
confidence: 99%